2015
DOI: 10.1371/journal.pone.0128526
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Dependence of Infarct Size and Acute Heart Failure in ST Elevation Myocardial Infarction

Abstract: ObjectivesThere are conflicting data on the relationship between the time of symptom onset during the 24-hour cycle (circadian dependence) and infarct size in ST-elevation myocardial infarction (STEMI). Moreover, the impact of this circadian pattern of infarct size on clinical outcomes is unknown. We sought to study the circadian dependence of infarct size and its impact on clinical outcomes in STEMI.MethodsWe studied 6,710 consecutive patients hospitalized for STEMI from 2006 to 2009 in a tropical climate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 33 publications
5
42
1
Order By: Relevance
“…35 Nevertheless, the issue regarding circadian rhythms, infarct size, and mortality remains a field of open discussion with contrasting reports, probably affected by origin of the study population and other variables. 8,11,34,36 Other important issues that need clarification are the genetic and ethnic background, which could influence circadian rhythms and seasonal patterns, even if this study found that the pattern of a summer shift can be observed in different ethnic and genetic backgrounds. Discovering molecular pathways associated with diseases plays a pivotal role in understanding the relation between cardiological pathologies and genetic factors.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…35 Nevertheless, the issue regarding circadian rhythms, infarct size, and mortality remains a field of open discussion with contrasting reports, probably affected by origin of the study population and other variables. 8,11,34,36 Other important issues that need clarification are the genetic and ethnic background, which could influence circadian rhythms and seasonal patterns, even if this study found that the pattern of a summer shift can be observed in different ethnic and genetic backgrounds. Discovering molecular pathways associated with diseases plays a pivotal role in understanding the relation between cardiological pathologies and genetic factors.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, we did not record diabetic status, renal function, which can affect the levels of vitamin D, and if any subjects were taking vitamin D supplements or other drugs that could potentially affect the results, such as β‐blockers (populations of our study where these data were available accounted for <15%) and aspirin 32, 33. However, contrasting findings were reported regarding diabetic status and the absence of circadian rhythm, in particular the absence of an increased morning peak of STEMI incidence in diabetic patients 32, 33, 34. Finally, in our study we address STEMI incidence but not outcome (eg, death), which might be another interesting variable to consider.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Circadian rhythms have also been shown to play a major role in heart pathophysiology. This is illustrated by increased incidence of myocardial infarction in the morning compared to the evening [77][78][79], and a correlation between infarct size and the time of the day at which it occurs is noted [80][81][82]. Mice that overexpress a dominantnegative form of the CLOCK protein in cardiomyocytes specifically (CCM) show abolished rhythmicity in cardiac CCG expression, which results in an abrogated circadian response in infarct size after ischemia/reperfusion [36].…”
Section: The Circadian Clock In (Heart) Disease and Regenerationmentioning
confidence: 99%